Determinants of adverse event occurrence in children with short stature born small for gestational age treated with growth hormone - Coutant, Regis; Benchikh, Nazim; Linglart, Agnès; Nicolino, Marc; Salles, Jean-Pierre (Frontiers in Endocrinology, 2025)
IntroductionRecombinant human growth hormone (rhGH) treatment for short children born small for gestational age (SGA) is effective in improving height outcomes. Determinants of height response to rhGH treatment have been identified using multiple regression analyses. Although adverse events (AEs) associated with treatment have been described, determinants of AE occurrence are not well known.MethodsThis analysis used safety data collected between 2007 and 2018 in an observational, prospective registry study (NCT01578135) including children born SGA across 126 sites in France. AEs were reported by patients or recorded by treating physicians. Univariate and multivariate analyses were performed to identify determinants of occurrence of AEs and serious AEs (SAEs).ResultsOf 291 patients from the registry, 287 AEs were reported in 149 (51.2%) patients. Each patient experienced a mean of 0.205 AEs per patient-year (range 0–4.3) and a mean of 0.054 SAEs (range 0–1.8). The most frequently reported AEs were headache (9.3%) and arthralgia (4.5%). Using multiple regression analyses, longer registry participation (p=0.0146, odds ratio [OR]=1.98), presence of chronic disease (p=0.0004, OR = 2.56), and concomitant treatment (p=0.0162, OR = 1.79) were associated with increased risk of experiencing AEs. GH dose at inclusion or cumulative GH dose during first 2 years of treatment were not associated with AE risk, while higher GH dose at last visit was associated with reduced risk (p=0.0412, OR = 0.58).ConclusionsIn short children born SGA, underlying conditions and associated treatments seem to be the main factors associated with AE occurrence, while GH dose was inversely related to AE occurrence.